PENDIDIKAN ISLAM PADA MASA DINASTI UMAYYAH DAN DINASTI ABBASIYAH : FORMALISASI DAN INSTITUSIONALISASI - Azizah Aryati; Mindani; Dilly Yuwita Utami; Sherly Lisfitriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the development of Islamic education during the Umayyad and Abbasid Dynasties, which demonstrate distinct orientations, characteristics, and contributions to the advancement of Islamic knowledge. The main problem addressed in this study concerns how both dynasties developed educational systems that differed in structure yet remained interconnected in shaping the intellectual tradition of Islamic civilization. The purpose of this research is to describe the forms of educational institutions, learning methods, and the advancement of knowledge in each dynasty, as well as to analyze the factors that influenced these developments.This research employs a library research method by analyzing primary and secondary sources, including historical texts, academic books, and scientific articles related to Islamic educational history. Content analysis was used to categorize data into themes such as educational development, governmental policy, and scholarly contributions. The validity of the data was strengthened through source triangulation to ensure accuracy and consistency.The findings reveal that the Umayyad Dynasty laid the fundamental groundwork for Islamic education through traditional institutions such as kuttab, halaqah, and study circles that focused on teaching the Qur’an, Hadith, and Arabic language. Meanwhile, the Abbasid Dynasty elevated Islamic education to its golden age by establishing madrasahs, major libraries, observatories, and the House of Wisdom, which served as a center for translation and scientific development. This study concludes that the development of Islamic education during both dynasties represents an evolutionary and interconnected process that significantly contributed to the advancement of Islamic civilization.